2016
DOI: 10.4254/wjh.v8.i30.1287
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and activated effector T cells in chronic hepatitis C virus: Relation to autoimmunity

Abstract: AIMTo investigate how Tregs are regulated in chronic hepatitis C virus (HCV) patients via assessment of Tregs markers (granzyme 2, CD69 and FoxP3), Teffs markers [TNFRSF4 (OX40), INFG] and CD4, CD25 genes.METHODSA prospective study was conducted on 120 subjects divided into 4 groups: Group I (n = 30) treatment naïve chronic HCV patients; Group II (n = 30) chronic HCV treated with Peg/Riba; Group III (n = 30) chronic HCV associated with non-organ specific autoantibody and Group IV (n = 30) healthy persons as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Tsang and colleagues, in accordance with our results, reported an elevated Treg frequency in blood of chronic HCV patients with no correlation to liver function 22 . Similarly, Fouad et al in a recent Egyptian study showed that chronic HCV patients exhibited significant higher levels of circulating Tregs and FoxP3 expression in comparison to healthy control group which decreased significantly after peg-IFN ribavirin therapy 29 . Another Egyptian study found no correlation between circulating Tregs and any laboratory parameters including liver functions and viral load 30 .…”
mentioning
confidence: 77%
“…Tsang and colleagues, in accordance with our results, reported an elevated Treg frequency in blood of chronic HCV patients with no correlation to liver function 22 . Similarly, Fouad et al in a recent Egyptian study showed that chronic HCV patients exhibited significant higher levels of circulating Tregs and FoxP3 expression in comparison to healthy control group which decreased significantly after peg-IFN ribavirin therapy 29 . Another Egyptian study found no correlation between circulating Tregs and any laboratory parameters including liver functions and viral load 30 .…”
mentioning
confidence: 77%
“…In the context of liver autoimmune diseases marked by the presence of ANA, the loss of tolerance in the liver results from the loss of inhibitory functions of the immune system that results mainly from the decrease in quantity and function of the Treg cells ( Liberal et al., 2015 ). In patients with chronic HCV infection and ANA positivity, suppression of Treg cells was observed, with a reduction in cellular markers, including FOXP3 ( Fouad et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%